Implementation proposal of Sexual and Reproductive Health Consulting in rural areas - Romero Zarate, Gabriela (2022)
Objective: to systematize the implementation of procedures and decision-making of the perinatal specialist nurse, towards the community that attends the Concentrated Rural Health Center of Tepetitla de la Lardizabal, Tlaxcala for counseling in sexual and reproductive health. Method: Participatory Action Research was used, with 118 men and women between 15 and 45 years old, with convenience sampling. Results: Three phases were applied, corresponding to research with participants in the community, education and action; as a result, 16 diagnostic labels and flow chart of attention in the consultancy that are the basis of the proposed model were identified. Conclusions: this is a strategy that supports the practice, increasing the benefits of the discipline, supporting the clinical experience and allowing to improve the decision-making of the nursing professional, it is also evident that in the first level of attention the role of the nurse becomes important. by having theoretical knowledge which favors the optimal functional level of the user through teaching and presentation of care.